PENGARUH DISIPLIN BELAJAR SISWA TERHADAP PRESTASI BELAJAR PADA SISWA KELAS III SD NEGERI 040528 SUKADAME T.P. 2020/2021 - Restio - Sidebang (ELEMENTARY SCHOOL JOURNAL PGSD FIP UNIMED, 2021)
The research objective was to determine the description of student learning discipline, the description of student learning achievement, and the significant influence of learning discipline on the learning achievement of third grade students SD Negeri 040528  Sukadame in the 2020/2021 learning year. This type of research is a quantitative study with a population of third grade students SD Negeri 040528 Sukadame  and the sampling used was total sampling with a total of 17 students. The method used is descriptive analysis, using the t test formula. The average score of students is 78. The description of student learning achievement based on the average score of the semester report cards is 78, including the good category, and there is a significant influence between Student Discipline on Student Learning Achievement in class III SD Negeri 040528  Sukadame.